Convivendo com o portador de fissura lábio-palatal: o vivencial da enfermeira Linving together with the porter of cleft Lip and palate: the life of the nurse - Wilza Carla Spiri; Maria Madalena Januário Leite (SciELO, 1999)
O presente estudo teve como objetivo compreender o vivencial das enfermeiras na assistência ao portador de fissura lábio-palatal. Para tal utilizamo-nos de uma abordagem qualitativa na vertente da fenomenologia. Para o resgate das falas realizamos entrevistas com nove sujeitos, participantes do estudo, e norteadas pela questão: "Como é para você cuidar/ assistir, pacientes com fissura de lábio e ou palato ?" Os temas que emergiram revelaram a essência do fenômeno na perspectiva da enfermeira, possibilitando, através de um programa de educação continuada, a melhoria da qualidade da assistência. The purpose of this study was to understand the life of nurses in assisting the porter of cleft lip and palate In order to so we decided for a qualitative approach in the methodology of phenomenology. We interviewed nine subjects who took part of this study and their interviews were guided by this question: "How is it like to watch over/ take care of patients with cleft lip and or palate?"; The themes that emerged revealed the essence of the phenomenon in the nurse's perspective searching with the careful meanings to contribute to the improvement of assistance quality, thus offering subsidies to the developmente of a continuos educational program to the nursing team (staff)